2008
DOI: 10.1088/1475-7516/2008/04/015
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cosmic strings in the CMB with the Canny algorithm

Abstract: Line discontinuities in cosmic microwave background anisotropy maps are a distinctive prediction of models with cosmic strings. These signatures are visible in anisotropy maps with good angular resolution and should be identifiable using edge detection algorithms. One such algorithm is the Canny algorithm. We study the potential of this algorithm to pick out the line discontinuities generated by cosmic strings. By applying the algorithm to small-scale microwave anisotropy maps generated from theoretical models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 53 publications
2
63
0
Order By: Relevance
“…Depending on the sensitivity of the edge detection algorithm to the temperature edges, a bound on the cosmic string tension could then be imposed. This work is a continuation of a previous study [37] which indicated that an edge detection method may lead to a significant improvement in the sensitivity to the presence of cosmic strings compared to previous direct searches for strings in the CMB. In this paper we improve the method proposed in [37] and we investigate its application to surveys with a different set of specifications than those examined in that initial work.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Depending on the sensitivity of the edge detection algorithm to the temperature edges, a bound on the cosmic string tension could then be imposed. This work is a continuation of a previous study [37] which indicated that an edge detection method may lead to a significant improvement in the sensitivity to the presence of cosmic strings compared to previous direct searches for strings in the CMB. In this paper we improve the method proposed in [37] and we investigate its application to surveys with a different set of specifications than those examined in that initial work.…”
mentioning
confidence: 66%
“…The SPT is designed to provide 1 ′ resolution in the maps of the CMB, making it ideal to search for the KS-effect. Based on previous results [37], we believe that with such high resolution data our method could provide bounds on the cosmic string tension competitive with those of pulsar timing.…”
mentioning
confidence: 72%
“…These strings -if stable -would achieve a scaling solution (constant number of strings crossing each Hubble volume at each time [85][86][87]). Such strings give rise to linear discontinuities in the CMB temperature maps [169], lines which can be searched for using edge detection algorithms such as the Canny algorithm (see [170] for recent feasibility studies).…”
mentioning
confidence: 99%
“…Various methods have been developed to search for stringinduced contributions to the CMB, from power-spectrum constraints (Lizarraga et al 2014a(Lizarraga et al ,b, 2016Charnock et al 2016), to higher-order statistics such as the bispectrum (Planck Collaboration XXV 2014; Regan & Hindmarsh 2015) and trispectrum (Fergusson et al 2010), and tools such as edge detection (Lo & Wright 2005;Amsel et al 2008;Stewart & Brandenberger 2009;Danos & Brandenberger 2010), Minkowski functionals (Gott et al 1990;Ducout et al 2013;Planck Collaboration XXV 2014), wavelets and curvelets (Starck et al 2004;Hammond et al 2009;Wiaux et al 2010;Planck Collaboration XXV 2014;Hergt et al 2016), level crossings (Sadegh Movahed & Khosravi 2011), and peakpeak correlations (Movahed et al 2013). Current constraints on the string tension depend on the string model and simulation technique adopted.…”
Section: Introductionmentioning
confidence: 99%